Pengaruh Leverage Dan Likuiditas Terhadap Profitabilitas Pada PT Diamond Food Indonesia Tbk Periode 2020 – 2022 (Jurnal Kendali Akuntansi, 2023)
PT Diamond Food Indonesia Tbk is a company engaged in the food and beverage industry. The company's purpose in general is to increase profitability. However, there are several factors that can affect the profitability. The purpose of this study was to know and analyze the influence of leverage and liquidty on profitability at PT Diamond Food Indonesia Tbk simultaneously and partially. The type of data used is secondary data derived from the Financial Statements of PT Diamond Food Indonesia Tbk for the period 2020 – 2022. The research method used is quantitative descriptive analysis. The analyzer uses multiple linear regression equations, classical asumi tests, Detemination coefficient tests (R²), t tests (partial) and F tests (simultaneous). Data processing used SPSS version 25 program. Variable Leverage is measured using Debt Equity Ratio (DER), Liquidity is measured using the ratio namely Current Ratio (CR) and Profitability is measured using Return On Assets (ROA). Based on the results of the analysis with the t test (partial) shows that the variable leverage partially has no effect on profitability and the variable liquidity partially has a negative effect on profitability. Simultaneously showing variable results Leverage and Liquidity simultaneously have a significant effect on Profitability